The Effects of Flaxseed (Linum usitatissimum) -Supplement Diet on Blood Lipid in Cholesterol Fed Rats - Suaad M. J. Al-Hadrawy; Ikhlass A. Al-Hilaly; Haider A. Thanwan Al-Kafajy (Al-Qadisiyah Journal of Pure Science, 2018)
Currently there is considerable interest in the potential health benefits of oil seeds, such as soy and flaxseed, especially in relation to cardiovascular disease and cancer. We therefore evaluated health aspects of dietary flaxseed supplementation on blood lipid under prolonged hypercholesterolemic conditions in white rats.            Sixty male albino White rats were randomly assigned to four groups of five animals per feeding duration based on dietary treatment. Animals were fed for 0, 8, or 16 wk. The four diets included a control diet (CO) of regular rats chow, a 10% ground flaxseed-supplemented chow (FX), a 0.5% cholesterol-supplemented chow (CH), and a diet supplemented with 0.5% cholesterol and 10% ground flaxseed (FX+CH).            Blood samples were taken at baseline (0 wk) and after 8, or 16 wk of dietary intervention by cardiac puncture technique for measurement of serum triglycerides (TG), total cholesterol (TC), low density lipoprotein (LDL-C), high density lipoprotein (HDL-C), very low density lipoprotein (VLDL-C) and atherogenic index (TC/HDL-C). Serum TC, LDL-C, and the ratios TC/HDL-C increased in groups (CH) and (FX+CH) after weeks 8 and16 compared with time 0. Serum HDL-C decreased in group (CH) and increased in group (FX+CH)  compared with time 0. Serum TG and VLDL-C remained unaffected. Flaxseed- supplemented diet reduced the levels of serum cholesterol and LDL-C and the TC/HDL-C ratios after 8 and 16 weeks but increased the levels of HDL-C after 16 weeks in cholesterol-fed rats.            These data indicate that cholesterol feeding resulted in elevated serum TC, LDL-C, and the ratios TC/HDL-C. The flaxseed- supplemented diet reduced serum total cholesterol, LDL-C, and the ratios TC/HDL-C.